Increasing Investment Literacy Through Technical Analysis and Futures Trading Risk Management Education for Students: Peningkatan Literasi Investasi Melalui Edukasi Technical Analysis Dan Risk Management Perdagangan Berjangka Pada Mahasiswa - Revinda Keisya Safitri; Sugeng Purwanto (DPD Jatim Perkumpulan Dosen Indonesia Semesta, 2024)
Technological developments and a highly competitive economy have had the impact of facilitating investment. Generation Z, as a group that is very familiar with technology, is starting to pay attention to managing their finances, and has significantly increased their interest in investing. However, there are still many who have not learned the knowledge of how to analyze the market, face risks when investing, and how to choose a safe and legal broker. The investments made do not get maximum results, the investment money even decreases or there is nothing left. This gives rise to doubts and fears among some players about starting to invest again. This service aims to increase investment literacy among the Z generation group, especially students, through education on technical analysis and risk management of futures trading. This education explains how to analyze the market through technical analysis material, how to manage risk through risk management material, and provides tips for choosing a broker that is safe and whose legality is guaranteed.